2022
DOI: 10.1002/adfm.202207937
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structure Evolution and its Impact on the Electrochemical Performances of Aqueous‐Processed High‐Voltage Spinel LiNi0.5Mn1.5O4 Cathodes in Lithium‐Ion Batteries

Abstract: LiNi0.5Mn1.5O4 (LNMO) is a promising cathode in lithium‐ion batteries (LIBs) due to its high operating voltage and open Li+ diffusion framework. However, the instability of the electrode–electrolyte interface and the negative environmental impact of electrode fabrication processes limit its practical application. Therefore, switching electrode processing conditions to aqueous and understanding the accompanying surface structural evolution are imperative. Here, water‐treated, poly(acrylic acid) (PAA)‐treated, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The first charge/discharge profiles of LRH‐114 and LR‐114 in Figure 3 a show similar discharge capacities of around 300 mA h g −1 at 0.1 C (1 C = 250 mA g −1 ). Notably, the small discharge plateau at around 2.6 V for LRH‐114 is related to the spinel phase, [ 21 ] which is confirmed by the corresponding d Q /d V curve (Figure 3b). LRH‐114 exhibits better rate performance (Figure S9, Supporting Information), and the larger Li + diffusion coefficients ( D Li + ) derived from the GITT data (Figure S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 64%
“…The first charge/discharge profiles of LRH‐114 and LR‐114 in Figure 3 a show similar discharge capacities of around 300 mA h g −1 at 0.1 C (1 C = 250 mA g −1 ). Notably, the small discharge plateau at around 2.6 V for LRH‐114 is related to the spinel phase, [ 21 ] which is confirmed by the corresponding d Q /d V curve (Figure 3b). LRH‐114 exhibits better rate performance (Figure S9, Supporting Information), and the larger Li + diffusion coefficients ( D Li + ) derived from the GITT data (Figure S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 64%
“…X-ray photoelectron spectroscopy (XPS) analysis was carried out to further understand the surface chemical composition and the chemical valence states of the as-prepared samples, and Figure shows the corresponding results. The high-resolution F 1s spectrum (Figure a) could be deconvoluted into three peaks, the binding energy of C–F at 688.0 eV (binding with applied carbon sources for XPS testing), the binding energy of Li–F at 685.0 eV, and the binding energy of TM-F around 684.0–685.0 eV. The higher the LiF content added to LNMO, the higher the Li–F remaining on the surface of the LNMO particles. More interestingly, the ratio of TM-F bond intensity in the coating layer for LNMO-1.3LiF is larger than that of LNMO-2.6LiF, indicating that the surface chemical compositions of the coating layer will have an important role in the electrochemical performance of the as-prepared cathode materials.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Li-ion batteries using spinel oxide cathodes, irreversible S−R transformation was reported to block Li-ion transport and hence leads to capacity fading. 11,12 Nevertheless, for the oxygen evolution reaction (OER) of water splitting, a limiting reaction for green hydrogen production, 7 the S−R transformation could play an important role in promoting the catalytic activity of spinel oxide electrocatalysts. A typical example is the Co 3 O 4 spinel oxide, which represents one of the most active electrocatalysts for the OER.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Under the electrochemical conditions, it is shown that the spinel oxide surface may transform to a rocksalt phase, where the metal cations migrate from the tetrahedral sites to empty octahedral sites. This spinel-to-rocksalt (S–R) transformation was reported to significantly affect their electrochemical performance and degradation depending on its different reversibility under different conditions. For example, in Li-ion batteries using spinel oxide cathodes, irreversible S–R transformation was reported to block Li-ion transport and hence leads to capacity fading. , Nevertheless, for the oxygen evolution reaction (OER) of water splitting, a limiting reaction for green hydrogen production, the S–R transformation could play an important role in promoting the catalytic activity of spinel oxide electrocatalysts. A typical example is the Co 3 O 4 spinel oxide, which represents one of the most active electrocatalysts for the OER.…”
Section: Introductionmentioning
confidence: 99%